A new species of the genus Gekko Laurenti (Squamata: Sauria: Gekkonidae) from Guangxi, China - Yang, Jian-Huan (Zootaxa, 2015)
A new species of the genus Gekko is described on the basis of six specimens from Wuming county of Guangxi, southern China. Gekko kwangsiensis sp. nov. is distinguished from other congeners by a combination of the following characters: body relatively small (SVL 64.2–69.7 mm in adults), slender; nares in contact with rostral; internasal absent or single; postmentals two (rarely three), enlarged; interorbital scales between anterior corners of the eyes 29–31; dorsal tubercle rows 9–11; ventral scales between mental and cloacal slit 185–208; midbody scale rows 143–156; ventral scale rows 41–45; subdigital lamellae on first toe 11–13, on fourth toe 13–18; finger and toe webbing weakly developed; tubercles absent on upper surface of fore limbs and hind limbs; precloacal pores nine or ten in males, absent in females; postcloacal tubercle single; tubercles present on dorsal surface of tail base; subcaudals enlarged; dorsal surface of body with 9 or 10 thin light bands between nape and sacrum, and dorsal surface of tail with remarkable black and white bands. Data on the natural history of the new species are provided, and the number of species in the genus Gekko recorded from China is now 17.